Pembentukan Sikap Disiplin Siswa Pada Sekolah Berbasis Asrama - Fajar Ridho Fatan Faiz; Nurhadi Nurhadi; Abdul Rahman (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2021)
Boarding school education instills various kinds of values ​​and characters to improve student discipline, both while undergoing education at school and when completing education. This study aims to explain the formation of student discipline in boarding schools. This study uses a qualitative method with an ethnographic approach. Data collection comes from the results of participatory observation, documentation, and in-depth interviews. Data analysis used disciplinary mechanism theory and Foucault's Panopticon. The results of this study indicate that the active role played by the teacher council, vice principal for student affairs, and school administrators in enforcing school rules has a significant relationship in shaping student discipline attitudes. The formation of students' disciplined attitudes is reflected in the various activities found in Islamic boarding schools and schools. Not arriving late at school, performing prayers on time, dressing neatly, participating in afternoon apple activities, cleaning the environment, and not violating the rules that have been set are activities carried out by students in forming their disciplinary attitude. Discipline formation is also carried out through two disciplinary mechanisms, namely by supervision through rules and punishments.